Establishment of two forensic medicine OSCE stations on the subject of external post-mortem examination - Heide, S.; Lessig, R.; Hachmann, V.; Stiller, D.; Rönsch, M.; Stoevesandt, D.; Biolik, A.; Watzke, S.; Kellner, J. (International journal of legal medicine, 2018)
An improvement in quality of medical external post-mortem examinations among others can be achieved by more intensive training of medical students. Modern learning and teaching methods such as e-learning modules and SkillsLab stations should be used for this. The introduction of corresponding methods of assessment such as the OSCE procedure is necessary to test the success of learning. In Halle (Germany), two OSCE stations on the subject of external post-mortem examinations were introduced in 2016. The ‘practical external post-mortem examination’ station test skills and abilities students have learned during practical external post-mortem examination in small group classes on a simulation doll. At the ‘death certificate’ station, an original death certificate must be filled in, testing the knowledge, skills and abilities learned in the SkillsLab station and during e-learning. A total of 148 students took part in the test. At both stations, at least two thirds of the students (69.5 and 81.7%) were able to show good or very good test results. In addition to the strengths, a detailed evaluation of the test results showed that there were still deficits in terms of the corresponding courses (e.g. inspection of the neck region in the small group classes), which will have to be remedied in the future. When analysing the test concept and the test implementation, objectivity was nearly perfect. There was a satisfactory internal consistency and stability over 8 months. Ultimately, in addition to several strengths (such as good understanding and transparency of the checklists) the evaluation of the examiners also showed further potential areas for improvement (e.g. harmonisation of the degree of difficulty for the individual rotations) when designing the OSCE stations. Overall, it was possible to determine that the OSCE testing format is a suitable tool to test external post-mortem examination skills and that conclusions about improvements in teaching can also be drawn from this.